Efek Pemberian Dosis ZA pada Lahan Tercemar Logam Berat Timbal terhadap Pertumbuhan dan Akumulasi Pb pada Tanaman Puring (Codiaeum variegatum L.) dan Lidah Mertua (Sansevieria trifasciata L.) - Elina Uswatun Hasanah; Anis Rosyidah; Mahayu Woro Lestari (Folium : Jurnal Ilmu Pertanian, 2020)
AbstractThis research aimed to apply a phytoremediation process  by adding fertilizer to increase the biomass of hyperaccumulator plants. This research was an experiment conducted in the Greenhouse and Laboratory of  Faculty of Agriculture,University of Islam Malang which began in September to November 2018. This experiment used a factorial randomized block design (RBD) consisting of 2 factors. The first factor was the administration of several Doses of ZA consisting of three levels, namely control (P0), ZA 100 kg N ha-1 (P1), ZA 200 kg N ha-1 (P2) and the second factor of plant species consists of two levels, (puring plants (T1), lidah mertua plants (T2)). The results showed that the calculation of TF of Pb ranged from 0.64 to 0.95. It   is  categorized into phytoremediation phyto-stabilizationcategoy.  The optimal dosage of ZA for puring plants needed was 95 kg N ha-1  with Pb Absorption 0,43875 ppm, whole the optimal dosage of ZA for lidah mertua plants was 116,7 kg N ha-1 with Pb absorbtiohn  0,37383 ppm.  Keywords: ZA fertilizer, Pb accumulation, Codiaeum variegatum L., Sansevieria trifasciata L.